From cancer therapy to cardiac safety: the role of proteostasis in drug-induced cardiotoxicity - Qian, Xingyu; Yao, Mengdong; Xu, Jingyu; Dong, Nianguo; Chen, Si (Frontiers in Pharmacology, 2024)
Drug-induced cardiotoxicity (DICT) poses a significant challenge in the prognosis of cancer patients, particularly with the use of antineoplastic agents like anthracyclines and targeted therapies such as trastuzumab. This review delves into the intricate interplay between drugs and proteins within cardiac cells, focusing on the role of proteostasis as a therapeutic target for mitigating cardiotoxicity. We explore the in vivo modeling of proteostasis, highlighting the complex intracellular environment and the emerging techniques for monitoring proteostasis. Additionally, we discuss how cardiotoxic drugs disrupt protein homeostasis through direct chemical denaturation, endoplasmic reticulum stress, unfolded protein response, chaperone dysfunction, impairment of the proteasome system, and dysregulation of autophagy. Finally, we provide insights into the applications of cardioprotective drugs targeting proteostasis to prevent cardiotoxicity and the adoption of structural proteomics to evaluate potential cardiotoxicity. By gaining a deeper understanding of the role of proteostasis underlying DICT, we can pave the way for the development of targeted therapeutic strategies to safeguard cardiac function while maximizing the therapeutic potential of antineoplastic drugs.